An evaluative study of the educational media programs in selected member institutions of the Philippine Universities Audiovisual Center (PUAVC) - Pasamba, Maria Gloria (1987)
The educational media programs of selected institutions, according to the Proposed Minimum Standards set by PUAVC were evaluated in this study. The evaluation includes the present status of the program, the condition of its resources, materials and other facilities, and the management objectives of the media programs
Thesis (M.Ed.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: Philippine Universities Audiovisual Center; Media programs (Education).